Clinical characteristics and care pathways of patients with personality disorder who died by suicide. Issue 2 (March 2020) - Flynn, Sandra; Graney, Jane; Nyathi, Thabiso; Raphael, Jessica; Abraham, Seri; Singh-Dernevik, Sandeep; Williams, Alyson; Kapur, Nav; Appleby, Louis; Shaw, Jenny
Abstract : Background: It is estimated that 1 in 10 people have a personality disorder. People with emotionally unstable personality disorder are at high risk of suicide. Despite being frequent users of mental health services, there is often no clear pathway for patients to access effective treatments. Aims: To describe the characteristics of patients with personality disorder who died by suicide, examine clinical care pathways and explore whether the care adhered to National Institute for Health and Care Excellence guidance. Method: National consecutive case series (1 January 2013 to 31 December 2013). The study examined the health records and serious incident reports of patients with personality disorder who died by suicide in the UK. Results: The majority had a diagnosis of borderline/emotionally unstable or antisocial personality disorder. A high proportion of patients had a history of self-harm ( n = 146, 95%) and alcohol ( n = 101, 66%) or drug misuse ( n = 79, 52%). We found an extensive pattern of service contact in the year before death, with no clear pathway for patients. Care was inconsistent and there were gaps in service provision. In 99 (70%) of the 141 patients with data, the last episode of care followed a crisis. Access to specialised psychological therapies was limited; short-term in-patient admissions was adhered to; however, guidance on short-term prescribing for comorbid conditions was not followed for two-thirds of patients. Conclusions: Continuity and stability of care is required to prevent, rather than respond to individuals in crisis. A comprehensive audit of services for people with personality disorder across the UK is recommended to assess the quality of care provided.